Investigation on current transformers for measuring of electron beam pulse current - P. Nanthanasit (2020)
© Published under licence by IOP Publishing Ltd. The radio-frequency (RF) linear accelerator (linac) system of the PBP-CMU Electron Linac Laboratory at the Plasma and Beam Physics Research Facility is used as an injector system for future mid-infrared and terahertz free-electron lasers. The properties of electron beams produced from the linac must be controlled appropriately to produce high-quality radiation. One of the most important properties is the electron pulse current that can be measured using a current transformer. A copper wire with proper insulator is wounded around the ferrite-core forming a secondary coil of the current transformer. The electron beam passing through the transformer acts as the current in the primary coil and it induces an electromotive force in the secondary coil. Therefore, the output signal from the secondary coil can be measured and analyzed to be a pulse current of electron beam. The measured current pulse shape and value strongly depend on the characteristics of the current transformer. This study focuses on testing and calibrating of existing current transformers installed in the linac system. In the experiments, the pulse generator was used to generate the input pulse current with various pulse lengths. The output pulses were then sampled with a digital oscilloscope. The experimental results showed that the output pulses from the current transformers have distort shape compared with the input pulses. Consequently, the correction was conducted to provide more accuracy of the measuring value of the electron pulse current. The results of this research can be used as a valuable database for the existing current transformers and to develop the new ones that can provide more accurate results.